Foundation Technology Development Of Hydraulic Structure On Peat Soil - Mahdi Ibrahim Tanjung; Nurlia Sadikin; Dery Indrawan (JURNAL TEKNIK HIDRAULIK, 2016)
Many hydraulic structures in Indonesia are built on peat soil, especially in Sumatra, Kalimantan and Papua. This soil has bad geotechnical characteristic for building foundation, because its low of shear strength, high potential of land subsidence and consolidation occured in a long term. One way to overcome this issues is using pile foundation. Therefore, a research was conducted in order to found foundation technology of hydraulic structure for peat soil using cerucuk, sand pile and concrete pile. This development of technology being conducted using geotechnical investigation and numerical modeling. The usage would be more effective when embankment strain is distributed evenly and not concentrated on the center of embankment. The search of alternative foundation is narrowed to the efficiency of the foundation design and the methods of implementation. Physical model results show that support capacity of the pile did not significantly increased in every increment in length, the increase instead happened when the tip of the pile deep in mineral soil layer below the peat layer. The foundation type made of concrete firmly in place give a supporting capacity 4 times compared to pile, while combination of pile with sand increase the pile supporting capacity to 2 times only, and pile of sand covered with PVC pipe has a supporting power that is almost the same with pile. Based on that, the concrete foundation type casted in place can be substitute alternative for pile.